HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN LEMPAR LEMBING PADA SISWA SMA NEGERI 2 TOMIA - Ardi Darmawan; Asmuddin; Badaruddin (Universitas Halu Oleo, 2021)
The purpose of this research was to determine the correlation between arm muscle strength and javelin throw ability at the students of SMA Negeri 2 Tomia. The population in this research were all students of SMA Negeri 2 Tomia was obtained 424 students consist of 204 boys and 220 girls. The sample in this study was taken based on purposive random sampling where selected based on the consideration of the male gender, and the students which could done pull ups properly and correctly were to 105 people. Furthermore, it was carried out randomly then that 31 people were obtained as samples in this study. The instrument used to measure of arm muscle strength was the pull up test for 60 seconds and to measure javelin throw ability was to javelin throw test as long as 3 times and the best throw was taken. The research data were analyzed by using the product moment statistical technique at a significant level of 0.05. Based on the results obtained from hypothesis testing, it shows that rxy = 0.51 > rtable at the significant level of 0.05 = 0.355. The coefficient determination of arm muscle strength with javelin throw ability is 0.26 or 26%. Its means that 26% of javelin throw ability is influenced by arm muscle strength, while 0.74 or 74% is influenced by other biomotor elements. The research can be concluded that there is a significant correlation between arm muscle strength and javelin throw ability at the students of SMA Negeri 2 Tomia.